A BASELINE STUDY ON CORAL REEF FISHES IN THE MARINE PROTECTED AREAS IN SOUTHERN CEBU, PHILIPPINES - Corrales, Christine M.; Delan, Gloria G.; Rica, Rachel Luz V.; Piquero, Alfonso S.; Monte, Irene A. (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 17 No. 1, 2014, 2018)
Marine protected areas in the sampling sites have been established 8-13 years ago. This study was conducted to have a baseline information on the diversity, density and biomass of coral reef fishes inside and outside the five marine protected areas (MPAs) of Casay, Argao; Cawayan, Dalaguete; Daan-Lungsod Guiwang, Alcoy; North Granada, Boljoon and Sta. Cruz, Ronda (Control). Coral reef fishes in the MPAs were identified using Fish Visual Census Method. Results of the t - test showed that the mean diversity (fish species/250m2) of target and non-target fish species found in areas inside and outside the MPAs were significantly different. In terms of target species, the inside and outside density showed no significant difference. Similarly, density (ind./1,000m 2) of  non-target  species  inside  and  outside  also  showed  no  significant  difference.  This  is  an indication that fish density inside and outside the MPAs were more or less of the same condition. The  mean  biomass  (kg/1,000m2) of  target  species  inside  and  outside  the  MPAs  showed  a significant difference  in  contrast with non-target species inside and outside the MPAs which showed a no significant difference. Higher biomass of target fish species belonging to family Caesonidae  (fusiliers) and Scaridae (parrotfishes)  were commonly observed  inside the MPAs. Results showed that fish species were more diverse with higher density and biomass inside the MPAs than the outside area. However, fish diversity and density were contributed mostly by non - target species. Hence, the need for a long-term protection and a well-managed MPA to improve fish population in terms of diversity, density and biomass specifically, target fish species.